Incremental prognostic value of downstream PET perfusion imaging after coronary CT angiography - Lehtonen Eero; Kujala Iida; Tamminen Jonne; Maaniitty Teemu; Saraste Antti; Teuho Jarmo; Knuuti Juhani; Klén Riku (OXFORD UNIV PRESS, 2025)
Purpose: To evaluate the incremental value of positron emission tomography (PET) myocardial perfusion imaging (MPI) over coronary computed tomography angiography (CCTA) in predicting short- and long-term outcome using machine learning (ML) approaches.
Methods: 2411 patients with clinically suspected coronary artery disease (CAD) underwent CCTA, out of whom 891 patients were admitted to downstream PET MPI for hemodynamic evaluation of obstructive coronary stenosis. Two sets of Extreme Gradient Boosting (XGBoost) ML models were trained, one with all the clinical and imaging variables (including PET) and the other with only clinical and CCTA-based variables. Difference in the performance of the two sets was analyzed by means of area under the receiver operating characteristic curve (AUC).
Results: After the removal of incomplete data entries, 2284 patients remained for further analysis. During 8-year follow-up, 210 adverse events occurred including 59 myocardial infarctions, 35 unstable angina pectoris, and 116 deaths. The PET MPI data improved the outcome prediction over CCTA during the first 4 years of observation time and the highest AUC was at the observation time of year 1 (0.82, 95% CI 0.804 - 0.827). After that, there was no significant incremental prognostic value by PET MPI.
Conclusion: PET MPI variables improve the prediction of adverse events beyond CCTA imaging alone for the first 4 years of follow-up. This illustrates the complementary nature of anatomic and functional information in predicting outcome of patients with suspected CAD.